Frontlines and Crossroads: The Impact of COVID-19 on the Motivations of Medical Students from Selected Philippine Medical Schools in Pursuing Their Medical Studies - Adriel Cheng; Ysabelle Bianca Andan; Kristine Go; Yeoj Luces; Jeanne Peralta; Jeremy Sumang; Manuel Dayrit (International Journal of Medical Students)
Background: Because the COVID-19 pandemic forced Philippine medical education to shift online, the loss of practical skills and face-to-face clinical interactions affected many students who had to cope with both lifestyle and learning changes. This study aimed to compare the strength and nature of motivations of medical students to pursue their studies before and after the onset of the pandemic, and to propose recommendations to support them through the pandemic and beyond.